Determination of the distribution angiotensin-converting enzyme (ACE I/D) and alpha-actinin-3 (ACTN-3 R577X) among elite sprinters and middle-long distance runners in Turkey - (:unkn) unknown (MATTIOLI 1885, 2020)
Study Objectives: The purpose of this study was to define ACTN3 and ACE genes affecting the athletic performance of sprinters and mid-long distance athletes. Methods: A total of 184, elite sprinters and mid long distance athletes and sedantary participated in the study. Subjects were categorized into three groups as sprinters, mid-long distance athletes, and sedantary. After DNA isolations, the Single PCR technique was used for ACE genotyping and Real Time PCR was used for ACTN3 genotyping. Results: The R allele of the ACTN3 gene was found to be high for sprinters. The allele of ACE D gene was high for distance athletes. Conclusion: ACTN3 and ACE genes allele distributions of sprinters and distance athletes were determined in relation with speed for the R allele of ACTN3 and with endurance for the D allele of the ACE gene.
Keywords: Sprinter; Mid-Long Distance Runners; ACTN3; ACE; ENDURANCE PERFORMANCE; NO ASSOCIATION; POLYMORPHISM; GENE; GENOTYPES